Structural design of RCC building using integrated BIM-based design workflow and analysis result comparison between ETABS and RSAP - Muhammad Yousaf,; Mohammad Sohail,; Muhammad Tayyab,; Muhammad Javedan,; Muhammad Habib, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Rapid computerization and stakeholder integration in the construction industry stressed the need for a new design methodology that was only possible through BIM. To address the inefficiency and limitations of conventional design flow that lead to design clashes, information loss, delays, and poor stakeholders’ coordination throughout the design phase, as well as the designer’s reluctance to use BIM-integrated software for design. This study aims to develop an integrated design flow using the Autodesk system followed by structural design through the developed flow. Further, the study also aims to identify and resolve design clashes between architectural and structural models and incorporate analysis results comparison of RSAP and ETABS. The results of the study revealed that BIM design flow provided better coordination between stakeholders, speedy clash detection, and resolved bi-directional interoperability issues using an extension (structural analysis toolkit). Furthermore, design through BIM provided better visualization i.e., both 2D and 3D, and final documentation in the shape of structural detailing of designed elements. Navisworks successfully identified coordinate and element clashes between architectural and structural models and provided a virtual 3D representation of the facility before the construction phase. The analysis results of RSAP and ETABS revealed that RSAP gives higher analysis results than ETABS due to the different analysis procedures of the two software packages thus yielding safer design.